Pan-cancer analysis reveals DDX21 as a potential biomarker for the prognosis of multiple tumor types - Hu, Ankang; Wang, Yonghui; Tian, Jiahao; Chen, Zihan; Chen, Renjin; Han, Xufeng; Chen, Yang; Liu, Tingjun; Chen, Quangang (Frontiers in Oncology, 2022)
Background DExD-box helicase 21 (DDX21) is an essential member of the RNA helicase family. DDX21 is involved in the carcinogenesis of various malignancies, but there has been no comprehensive research on its involvement in different types of cancer. Method This study used TCGA, CPTAC, GTEx, GEO, FANTOM5, BioGRID, TIMER2, GEPIA2, cBioPortal, STRING, and Metascape databases and Survival ROC software to evaluate DDX21 gene expression, protein expression, immunohistochemistry, gene mutation, immune infiltration, and protein phosphorylation in 33 TCGA tumor types, as well as the prognostic relationship between DDX21 and different tumors, by survival analysis and similar gene enrichment analysis. Furthermore, Cell Counting Kit-8 (CCK-8) and Transwell studies were employed to assess the effect of DDX21 expression on lung adenocarcinoma (LUAD) cell proliferation and migration. Result The DDX21 gene was highly expressed in most cancers, and overexpression was associated with poor overall survival (OS) and disease-free survival (DFS). DDX21 mutations were most common in uterine corpus endometrial carcinoma (UCEC; >5%), and DDX21 expression was positively correlated with the degree of infiltration of CAF and CD8+ cells in several tumor types. Numerous genes were co-expressed with DDX21. Gene enrichment analysis revealed close links between DDX21, RNA metabolism, and ribosomal protein production. In vitro analysis of LUAD cells showed that DDX21 expression was positively correlated with cell proliferation and migration capacity, consistent with prior bioinformatics studies. Conclusions DDX21 is overexpressed in a variety of cancers, and overexpression in some cancers is associated with poor prognosis. Immune infiltration and DDX21-related gene enrichment analyses indicated that DDX21 may affect cancer development through mechanisms that regulate tumor immunity, RNA metabolism, and ribosomal protein synthesis. This pan-cancer study revealed the prognostic value and the oncogenic role of DDX21.